Respostas

2014-01-24T19:17:31-02:00
Letra c : 

x²+9x+8=0 ~> a = 1 , b = 9 , c = 8

Δ = b² - 4ac
Δ = 9² - 4.1.8
Δ = 81 - 32
Δ = 49

x = -b ± √Δ
         2a

x = -9 ± √49
          2.1

x = -9 ± 7
        2

x' = -9 + 7  = -
= -1                 x" = - 9 - 7  = -16 = -8
         2          2                                    2         2


Letra d : 

x²-14x+48=0 ~> a = 1 , b = -14 , c = 48

Δ = b² - 4ac
Δ = (-14)² - 4.1.48
Δ = 196 - 192
Δ = 4

x = -b ± √Δ
          2.a

x = -(-14) ± √4
            2.1

x = 14 ± 2
         2

x' = 14 + 2  = 16 = 8             x" = 14 - 2  = 12  = 6
          2          2                             2          2


Letra e :

x²+3x-28=0 ~> a = 1 , b = 3 , c = -28

Δ = b² - 4ac
Δ = 3² - 4.1.(-28)
Δ = 9 - (-112)
Δ = 121

x = -b 
± √Δ
          2a

x = -3 
± √121
          2.1

x = -3 
± 11
          2

x' = -3 + 11 = = 4                    x" = -3 - 11 = -14 = -7
          2         2                                      2         2

1 5 1